(untitled) (Research, Society and Development, 2022)
Senna occidentalis Link (Fabaceae), known as “fedegoso”, is used in folk medicine due to its anti-inflammatory, antioxidant, muscle relaxant and inhibiting lipid peroxidation imputed to flavonoids contained in its composition. The species is also a constituent of processed products are commercialized in various parts of the world including Brazil, although there are few reports in the literature about the development of an analytical method for quantification of flavonoids in it. The main purpose of this research was the evaluation of an analytical methodology to determinate the content of total flavonoids in leaves of S. occidentalis, for quality control. The parameters evaluated were: drug: solvent ratio, concentration of aluminum chloride and reaction time. The quantification of total flavonoids was obtained after reaction with aluminum chloride by UV/Vis spectrophotometry. The results revealed a maximum absorption peak (λ = 392 nm) was the amount of 0.5 g of a plant raw in 100 mL of solvent and there were no significant influences between the concentrations of aluminum chloride or hydroalcoholic solutions analyzed. The evaluation of reaction time allowed to characterize the kinetics as slow, stabilizing from 60 min, choosing this as reading time. The method was specific, linear, precise, accurate and robust, according to the specifications set in RDC n. 166/2017. Finally, the results of the study showed that the measured methodology is simple and accurate and can be applied for quality assessment of the species S. occidentalis.